Qili Qiangxin Capsule Combined With Sacubitril/Valsartan for HFrEF: A Systematic Review and Meta-Analysis - Qian Xiang; Qian Xiang; Qian Xiang; Mengxi Wang; Mengxi Wang; Mengxi Wang; Yuhan Ding; Yuhan Ding; Yuhan Ding; Manlu Fan; Manlu Fan; Manlu Fan; et al. (Frontiers in Pharmacology, 2022)
Background: Heart failure with reduced ejection fraction (HFrEF) is a complex, chronic disease and is among the top causes of morbidity and mortality. Angiotensin receptor-neprilysin inhibitor drugs represented by sacubitril/valsartan are the key drugs for the treatment of HFrEF in western medicine, and Qili Qiangxin Capsule (QQC) is a vital drug for the treatment of HFrEF in Chinese medicine. In recent years, there have been many relevant clinical studies on the combination of the two in the treatment of HFrEF. There are no systematic reviews or meta-analyses specific to sacubitril/valsartan combined with QQC for the treatment of HFrEF, so there is an urgent need to evaluate the effectiveness and safety of these two drugs.Objective: To systematically assess the safety and effectiveness of QQC combined with sacubitril/valsartan in the treatment of HFrEF through a meta-analysis.Methods: Searching studies on the combination of QQC and sacubitril/valsartan in the treatment of HFrEF, from databases such as PubMed, Cochrane Library, Web of Science, Wanfang Databases, Chinese Biomedical Literature Database, China Science and Technology Journal Database, and China National Knowledge Infrastructure, prior to 31 October 2021. Two reviewers regulated research selection, data extraction, and risk of bias assessment. Review Manager Software 5.4 was used for meta-analysis.Results: There were 26 studies with 2,427 patients included in total. The meta-analysis showed the combination therapy has significant advantages in improving the clinical efficacy, 6-MWT (RR = 1.18, 95% CI: 1.11–1.26, MD = 70.65, 95% CI: 23.92–117.39), superior in ameliorating LVEF, LVEDD, LVESD, and SV (LVEF: MD = 5.41, 95% CI: 4.74–6.08; LVEDD: MD = −4.41, 95% CI: −6.19 to −2.64; LVESD: MD = −3.56, 95% CI: −4.58 to −2.54; and SV: MD = 5.04, 95% CI: 3.67–6.40), and in improving BNP, NT-proBNP, AngII, and ALD (BNP: MD = −97.55, 95% CI: −112.79 to −82.31; NT-proBNP: MD = −277.22, 95% CI: −348.44 to −206.01; AngII: MD = −11.48, 95% CI: −15.21 to −7.76; and ALD: MD = −26.03, 95% CI: −38.91 to −13.15), and all the differences have statistical advantages (p < 0.05). There are no advantages in improving CO and adverse events (MD = 0.66, 95% CI: −0.12 to 1.43 and RR = 0.62, 95% CI: 0.37–1.04, respectively), and the differences have no statistical advantages.Conclusion: Compared with the control group, QQC combined with sacubitril/valsartan may be effective in the treatment of HFrEF. However, the conclusion of this study must be interpreted carefully due to the high risk and ambiguity of bias in the included trials.